IN VITRO SULFORHODAMINE B ASSAY EVALUATION OF NOVEL 2-PHENYL BENZOFURANONE DERIVATIVES ON HUMAN SKIN CANCER CELL LINE G361. - DOONABOYINA, RAGHAVA; Mittal, Abhilasha; Gummadi, Sridhar Babu (Journal of Drug Delivery and Therapeutics, 2019)
The newly synthesized compounds are being tested for in vitro anticancer activity. The method used for In Vitro testing is Sulforhodamine B assay also known SRB assay. Cell lines were prepared and homogenized and disassociated with the help of trypsin. Then trypsin was inactivated with fetal bovine serum. Then cell concentration was determined. Synthesized molecules were prepared into four different dilutions and exposed to cell lines. The procedure was also compared with standard drug doxorubicin. All the cell medium were incubated 37 degrees centigrade in a humidified incubator with 5 percentage CO. The plates were stained and fixed with trichloroacetic acid. Finally, the plates were incubated in orbital shaker incubator and absorbance was measured in a microplate reader at 510nm. All compounds (1-30) showed the similar anticancer activity of compounds (IA, IB, ID, IE, IF, IIB, IIC, IIIA, IVB, IVF, VA, VC, VD, VE.) were more potent when compared to the rest of the compounds synthesized.